Diagnosis Miskonsepsi Siswa pada Materi Kalor dengan Menggunakan Three-Tier Essay dan OpenâEnded Test Items - Fitriah, Lutfiyanti (Universitas Lambung Mangkurat, 2017)
The purpose of this research is to identify studentâs misconceptions on heat subject matter. For identifying student misconception, heat conceptual test instruments are developed. These test are three-tier essay and open-ended test items. These tests are validated by expert and tested empirically to 94 students. Based on empiric test, the validity, reliability, level of difficulty, and distinguishing matter are determined. The subject of this research is grade X Mathematics and Science Program SMAN 7 Banjarmasin that consists of 34 students in second semester of the academic year 2014/2015. This class is chosen by cluster random sampling. Data are analyzed qualitatively by data reduction, coding, data display, and conclusion drawing. Based on the data analysis, it is found that there are misconception and the test instruments can be used to identify student misconceptions.Â